Photoelectron angular distributions of ns subshells of open-shell atoms as indicators of interchannel coupling: Sc 4s photoionization - (:unkn) unknown (AMER PHYSICAL SOC, 2000)
It is shown that the photoelectron-angular distribution asymmetry parameter beta, arising from ns photoionization in open-shell atoms, is quite a bit more sensitive to interchannel coupling than the integrated cross section. An example of 4s photoionization of atomic Sc is presented. It is demonstrated that this effect can occur throughout the periodic system.
Keywords: CROSS-SECTIONS; SCANDIUM ATOM; APPROXIMATION